Language learning strategies by EFL secondary school learners in Tanzania: an exploratory account - Msuya, Erasmus Akiley (Brazilian English Language Teaching Journal)
This is an exploratory account of English as a Foreign Language learning strategies used by Tanzanian secondary school students. Data were gathered from 70 EFL learners in two ordinary level secondary schools in Tanzania, through a questionnaire inventory adapted from Oxford (1990). The data were then analyzed and results tabulated. Findings show that the majority of the respondents were using social strategies and relatively few were using compensation and memory strategies. The most popular social strategy was plasticizing English with others. As for the affective strategies, the most popular was talking to someone else about how one feels about English. Among the memory strategies, using new English words in a sentence was most popular unlike in cognitive strategies where initiating conversations in English was the most popular learning strategy. It was concluded that EFL learners in Tanzania do not have learning one language learning strategy suitable for all learners